Decreases in 15-lipoxygenase metabolites in Olmsted syndrome model rats. Issue 3 (March 2017) - Wakabayashi, Masato; Yoshioka, Takeshi; Higashino, Kenichi; Numata, Yoshito; Igarashi, Yasuyuki; Kihara, Akio
Highlights: Leukocytes infiltrated unaffected skin tissue of Ht rats. 15-LOX metabolite levels decreased in unaffected skin of Ht rats. Expression of the 15-LOX genes was reduced in unaffected skin of Ht rats. Expression of some cytokine/chemokine genes increased in unaffected skin of Ht rats. Abstract: Background: Olmsted syndrome (OS) is a congenital dermatosis characterized by palmoplantar keratoderma and periorificial keratotic plaque. TRPV3 (transient receptor potential vanilloid subtype 3) encodes a thermosensitive Ca 2+ channel and is the causative gene of OS. However, the molecular mechanism that causes the pathological development of OS is unclear. Objective: We aimed to investigate the molecular mechanisms underlying OS pathology from the perspective of lipid metabolism. Methods: Comprehensive lipidomics and microarray analyses were conducted on tissue samples from a non-lesional skin area of OS model rats ( Ht rats) and from wild type (WT) rats as the control. Results: Infiltration of leukocytes such as eosinophils and neutrophils and an increase in the fibrotic region were detected in the unaffected skin area of Ht rats compared with the WT rats. Among about 600 lipid species examined, the levels of 15-lipoxygenase (LOX) metabolites, the precursors of anti-inflammatory and pro-resolving lipid mediators, and dihydroceramides decreased by ≥16-fold in Ht rats compared with WT rats. Consistent with the decreases in the 15-LOX metabolites, expression levels of the genes that encode the 15-LOXs, Alox15 and Alox15b, were largely reduced. Conversely, increased expression levels were detected of Il36b, Ccl20, Cxcl1, and Cxcl2, which encode cytokines/chemokines, and S100a8 and S100a9, which encode the Ca 2+ binding proteins that are implicated in epidermal proliferation. Conclusion: The pro-inflammatory state in the unaffected skin of Ht rats caused by decreases in 15-LOX metabolites and increases in cytokines/chemokines may contribute to the pathogenesis of OS.